Motor learning through virtual reality in cerebral palsy – a literature review - Massetti,Thais (2014)
Cerebral palsy is a well-recognized neurodevelopmental condition beginning in early childhood and persisting throughout life. It is considered the most common non-progressive neurological disease of childhood. Subjects with cerebral palsy present complex motor skill disorders, the primary deficits being abnormal muscle tone that affects posture and movement, alterations of balance and of motor coordination, decrease in strength and loss of selective motor control, with secondary issues of contracture and bone deformity. This population may have difficulties in motor skill learning processes. Skill learning is learning as a result of repeated exposure and practice. Due to the increasing use of virtual reality in rehabilitation and the significance of motor development learning of subjects with cerebral palsy, we have recognized the need for studies in this area. The purpose of this study was to investigate the results of previous studies on motor learning using virtual reality with patients with cerebral palsy. Initially, 40 studies were found, but 30 articles were excluded, as they did not fulfil the inclusion criteria. The data extracted from the ten eligible studies is summarized. The studies showed benefits from the use of virtual reality in children with cerebral palsy in gross motor function and improvements in motor learning with skill transfer to real-life situations. Therefore, virtual reality seems to be a promising resource and a strategic option for care of these children. However, there are few studies about motor learning with virtual reality use. The long term benefits of virtual reality therapy are still unknown.